Percy Jackson and the Sea of monsters - Riordan, Rick. (London : Puffin Books, 2013)
Demi-god Percy Jackson and his friends must journey into the Sea of Monsters to save their camp. But first Percy will discover a secret that makes him wonder whether being claimed as Poseidon's son is an honor or a cruel joke.
Keywords: Hades, -- (Greek deity -- Fiction; Zeus, -- (Greek deity -- Fiction; Mythology, Greek -- Juvenile fiction; Camps -- Fiction; Fathers and sons -- Fiction; Friendship -- Fiction; Mythology, Greek -- Fiction; Poseidon (Greek deity) -- Fiction; Fantastic fiction